In searching of the world gatekeeper - Violeta Nikolova (Проблеми на постмодерността, 2014)
A number of notable scientists and researchers of the communication science take a central place in their writings on the topic of influencing and shaping public opinion, but also for the group response and the leaders of public opinion.